Pyrolysis Mechanism of Hemicellulose Monosaccharides in Different Catalytic Processes - Wang, Shurong; Ru, Bin; Lin, Haizhou; Sun, Wuxing; Yu, Chunjiang; Luo, Zhongyang (Chemical research in Chinese universities, 2014)
The pyrolysis behaviors of four different hemicellulose monosaccharides, namely, two pentoses（xylose and arabinose） and two hexoses（mannose and galactose） catalyzed by HZSM-5 were investigated. The effects of two different processes by which the catalyst comes into contact with the substrate, namely, mixed with monosaccha- ride（in-bed） or layered above monosaccharide（in situ）, were compared. Evolution characteristics of typical pyrolytic products（H20, CO2, acids, furans and aromatics） were achieved by thermogravimetry-Fourier transform infrared spectroscopy. The in-bed catalytic process significantly lowered the pyrolytic temperature and increased the produc- tion of furans and acids at a low temperature by enhancing dehydration, retro-aldol fragmentation and Grob fragmen- tation. During the in situ catalytic process, volatiles generated from monosaccharides passed through a catalyst bed and underwent further dehydration, decarboxylation, and decarbonylation, significantly lowering the yields of acids and furans. The yield of aromatics was enhanced, and the corresponding volatilization temperature was lowered, es- pecially under the in-bed catalytic conditions. Pentoses entered into the zeolite pores more easily than hexoses did because of their smaller molecular size; thus, the in-bed catalytic process drastically affected pentose pyrolysis.